Planning for development with prospective approach in Bolivia, Ecuador, Guatemala y Peru - Sánchez Mercado, Álvaro Cristian (2018)
The current research make an exploration about some concepts linked to strategic planning of countries and comparison of the Planning Systems and their strategic development planning for Bolivia, Ecuador Guatemala and Peru.For that purpose, in the first part a systematic review of definitions was made and in the second part a systematic review of planning systems of said countries from the juridical framework that cover it up to its working methodology. Finally, as a result, it has been determined that Guatemala is the only country that has defined an upward planning system and uses the foresight working methodology from lowest levels. In addition, it has been possible to determine that all countries, except Peru, have made an explicit reassessment of the ancestral or indigenous question. JEL Classification Codes: O21, P11, P21, P41, R58.